Treatment of anal dysplasia in HIV-positive men who have sex with men in a large AIDS reference centre. Issue 1 (2nd January 2017) - Willems, Nathalie; Libois, Agnès; Nkuize, Marcel; Feoli, Francesco; Delforge, Marc; DeWit, Stéphane
Abstract : Objectives: Over the last few decades, incidence of anal cancer among HIV-positive men has been on the rise. In this context, programmes of screening and treatment of anal dysplasia which is a precursor of anal cancer have been developed. The aim of our study was to describe the efficiency, side effects and outcome of anal dysplasia treatment in a population of HIV-positive men who have sex with men (MSM). Methods: We performed a retrospective study of HIV-positive MSM who received treatment for anal dysplasia between May 2010 and February 2014 in the Saint-Pierre University Hospital, Brussels. The different treatments used were electrocautery (ECA), infrared coagulation (IRC), surgical treatment and imiquimod. Results: Seventy-three HIV-infected MSM were included in the study, counting 62% of HGAIN. Median age was 41 years. Eighty-one per cent were on HAART. Median CD4 cell count was 525 cell/mm³, and 65% had undetectable viral loads. A total of 139 therapeutic interventions were recorded during the study period, and two-thirds of the enrolled patients received more than one treatment. At 540 days of follow-up, the rate of treatment response was 62%. Fifty per cent of the persistent HGAIN were metachronous lesions. No severe adverse events were recorded but frequent treatment-associated discomfort was reported, such as pain, self-limited bleeding, infection and anal irritation. Conclusion: Treatment of anal dysplasia appears to be safe and to offer short-term efficiency. However, its long-term efficiency remains unknown, especially in the HIV-positive population in which spontaneous clearance is lower and rate of recurrence higher.